Meningkatkan Kemampuan Gotong Royong dengan Metode Problem-Based Learning (PBL) Memakai Diskusi pada Materi Membangun Hidup yang Bermartabat Fase F Kelas XI SMA Saint John’s Catholic School BSD - Benedictus Kaneka Pasadona (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This study aims to determine how to improve the learning outcomes of 11th grade Anthony students at Saint John's Catholic School BSD in the 2024/2025 school year in Religious Education and Budi Pekerti subjects through the application of Problem Based Learning by discussing the material of building a dignified life. The research conducted was a classroom action research using two cycles. The stages in each cycle include planning, action implementation, followed by observation and reflection. In this study, the first and second cycles discussed the same topic, namely building a dignified life with the title Developing a Culture of Love. This research only focuses on 11th grade students of Saint John's School, totaling 25. Data collection is done by observation and also cognitive aspect assessment in the form of essays. As supporting data, documentation of activities will be carried out. The results of research using Project Based Learning can show an increase in mutual cooperation; collaboration between students can be seen through the comparison of cycles I and II, where there is an increase in the presentation of mutual cooperation elements by 19% and an increase in cognitive aspects by 21%.